Empires and exchanges in Eurasian late antiquity (Cambridge, United Kingdom)
xxxvii, 504 sayfa
Keywords: “The second phase of Roman-steppe relations began during the latter part of the fourth century, when Hunnic groups entered the western steppes, and lasted through the early sixth century. This “Age of Attila“ saw major shifts throughout Western Eurasia. Several decades after the battle of Adrianople, Huns moved into Europe and became unified early in the fifth century with a center of power in the Hungarian plain“--